Autologous Reconstruction and Visceral Transplantation for Management of Patients With Gut Failure After Bariatric Surgery. Issue 4 (October 2015) - Abu-Elmagd, Kareem M.; Costa, Guilherme; McMichael, David; Khanna, Ajai; Cruz, Ruy J.; Parekh, Neha; Fujiki, Masato; Hashimoto, Koji; Quintini, Cristiano; Koritsky, A. Darlene; Kroh, Matthew D.; Sogawa, Hiroshi; et al.
<x xml:space="preserve">Abstract</x> Objective: Bariatric surgery (BS) is currently the most effective treatment for severe obesity. However, these weight loss procedures may result in the development of gut failure (GF) with the need for total parenteral nutrition (TPN). This retrospective study is the first to address the anatomic and functional spectrum of BS-associated GF with innovative surgical modalities to restore gut function. Methods: Over 2 decades, 1500 adults with GF were referred with history of BS in 142 (9%). Of these, 131 (92%) were evaluated and received multidisciplinary care. GF was due to catastrophic gut loss (Type-I, 42%), technical complications (Type-II, 33%), and dysfunctional syndromes (Type-III, 25%). Primary bariatric procedures were malabsorptive (5%), restrictive (19%), and combined (76%). TPN duration ranged from 2 to 252 months. Results: Restorative surgery was performed in 116 (89%) patients with utilization of visceral transplantation as a rescue therapy in 23 (20%). With a total of 317 surgical procedures, 198 (62%) were autologous reconstructions; 88 (44%) foregut, 100 (51%) midgut, and 10 (5%) hindgut. An interposition alimentary conduit was used in 7 (6%) patients. Reversal of BS was indicated in 84 (72%) and intestinal lengthening was required in 10 (9%). Cumulative patient survival was 96% at 1 year, 84% at 5 years, and 72% at 15 years. Nutritional autonomy was restored in 83% of current survivors with persistence or relapse of obesity in 23%. Conclusions: GF is a rare but serious life-threatening complication after BS. Successful outcome is achievable with comprehensive management, including reconstructive surgery and visceral transplantation.